A Bayesian plotting method for fractional factorial data analysis. - Allen, Theodore T. (Journal of Quality Technology)
This paper proposes a plot based method for fractional factorial data analysis. The proposed plot is called a "response-probability model analysis plot" (RPMAP) because it displays the predicted responses associated with alternative models and decisions versus the model posterior probabilities. Benefits of the proposed method include unique information about whether the current state of model uncertainty and achievement of objectives warrants additional experimentation. Also, in some cases, the RPMAP leads to settings with arguably superior robustness to model uncertainty compared with normal probability plots or Posterior probability plots. The methods are illustrated using the well studied injection molding data and another real world case study. In both cases, new insights are gained with potential value to practitioners.